Managing technology-critical elements from electronic waste in Small Developing Island States: a burden or an opportunity? - Wosnick, Natascha; Curtis, Dorlan; Hauser-Davis, Rachel Ann (Frontiers in Marine Science, 2024)
Small Island Developing States (SIDS) face profound challenges from pollution, exacerbated by inadequate infrastructure and resource limitations. This paper examines the longstanding pollution issues plaguing SIDS, highlighting their vulnerability to environmental degradation due to underdeveloped waste management systems and unique oceanographic conditions. The case study of Eleuthera Island in The Bahamas illustrates these challenges vividly, showcasing the island’s struggle with e-waste management. This example reinforces the urgency of integrated strategies to enhance environmental resilience and sustainable development in SIDS. Emerging concerns include the proliferation of technology-critical elements (TCEs) in e-waste, driven by rapid urbanization and tourism growth. Despite their crucial role in technological advancement, TCEs pose significant recycling and management difficulties, particularly in the context of limited waste infrastructure. The paper also highlights the imperative for comprehensive regulatory frameworks and sustainable practices to mitigate pollution impacts and safeguard ocean and human health, particularly by shedding light on legislative gaps and opportunities for enhancing pollution control measures in The Bahamas.